Lectotypification of Coelogyne zhenkangensis and its conspecificity with Coelogyne lancilabia (Arethuseae, Epidendroideae, Orchidaceae) - Shu, Nan; Li, Rong (Phytotaxa, 2025)
The holotype of Coelogyne zhenkangensis, preserved at the Herbarium of the Institute of Botany (PE [barcode 00271824]), is an admixture. To align with the original diagnosis, we designate the flowers in the bag, the solitary inflorescence, and the illustrations on the holotype sheet as the lectotype. Coelogyne zhenkangensis is conspecific with Coelogyne lancilabia. Consequently, we place Coelogyne lancilabia under the synonym of Coelogyne zhenkangensis.